Rasio keuangan yang mengindikasikan perusahaan mengalami financial distress pada perusahaan manufaktur BEI 2015-2018 - Risal Susanto (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2020)
Financial distress is an initial situation in which a company experiences financial difficulties, especially in financing the company's operations, most people only know that the company loses if it has been declared failed by the court and declared bankrupt, actually before that phase there is an indication of bankruptcy known as financial distress. This study aims to obtain empirical evidence about the effect of financial ratios namely profitability ratios, leverage, liquidity, and activities on financial distress in manufacturing companies listed on the Indonesia Stock Exchange (IDX), research conducted during the period 2015-2018 with a total sample of 68 Data retrieval is done by the method of selecting purposive sampling data. The data analysis technique used in this study is multiple regression analysis. By using the SPSS application version 20. The results of this study indicate that profitability ratios, leverage ratios, and activity ratios affect financial distress, whereas liquidity ratios have no effect on financial distress. Keyword: CR, DER, financial distress, ROA, TATO